Proses Legislasi Perda Tentang Penyelenggaraan Pendidikan Khusus Dan Pendidikan Layanan Khusus Oleh DPRD Kabupaten Tanah Datar - Fadilatul Istiqamah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This research examines the legislative process of Tanah Datar District Regulation No. 1/2015 on Education Implementation, particularly Chapter IX which regulates Special Education and Special Service Education. The issue raised is the limited access to education for students with special needs and vulnerable groups in the region. This study aims to analyze the legislative stages of the local regulation, the actors involved, and the challenges of its implementation. The method used is a descriptive qualitative approach with data collection techniques through interviews, document studies, observation and literature review. The results show that the legislative process is carried out systematically, starting from issue identification, agenda setting, preparation of academic papers, to ratification. However, the implementation still faces obstacles, such as limited human resources, inadequate facilities and low public awareness of the importance of inclusive education. In conclusion, this local regulation is a progressive step in promoting an equitable and inclusive education system in Tanah Datar. However, its successful implementation depends on strengthening coordination between agencies, increasing the capacity of educators, providing an adequate budget and continuous evaluation.Keywords: Public Policy, Education Local Regulation, Special Education, Special Services,